Exploring The Importance Of Phonetic Symbols In English Language Learning - Yani Lubis; Eby Delyani Sitompul; Sania Oktavia Nasution (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
This article explores the importance of phonetic symbols in English language learning. In the context of English language acquisition, phonetic symbols serve as tools to depict language sounds in a clear and consistent manner. The main objective of this article is to delve into why phonetic symbols play a significant role in improving English pronunciation and comprehension skills. By analyzing the benefits and practical applications of phonetic symbols, this article aims to provide valuable insights and guidance for language learners and educators seeking to enhance their proficiency in English. This article delves into the significance of phonetic symbols in the process of learning the English language. Phonetic symbols serve as a visual representation of speech sounds, aiding learners in accurately producing and distinguishing sounds that may be unfamiliar or challenging. The article explores the benefits of incorporating phonetic symbols in English language instruction, such as improving pronunciation accuracy, enhancing listening skills, and promoting effective communication. Additionally, it highlights the role of phonetic symbols in developing learners' phonological awareness and their ability to decode and comprehend spoken English. By understanding the importance of phonetic symbols, educators can employ effective strategies to support learners in acquiring accurate pronunciation and fluency in English.